Thermoluminescence kinetic parameters of proton-irradiated germanium doped flat-shape optical fibres - Hassan, M.F.; Rahman, W.N.; Akagi, T.; Sulaiman, N.S.; Bradley, D.A.; Noor, N.M. (Elsevier, 2022)
Glow curve is a key element in thermoluminescence (TL) studies as it provides on-the-ground understanding on the trapping mechanism inside the crystal lattice and hence stability of the TL material. In the present work, luminescence mechanism of the in-house fabricated germanium doped (Ge-doped) ﬂat-shape silica optical ﬁbres have been investigated following irradiation by 150-MeV proton beams. Results of TL dose-response showed that there is a linear relationship between TL response and proton doses from 1 to 10 Gy, with a coefﬁcient of determination close to one. The structure of glow curve remains unchanged throughout the studied dose range with a maximum glow peak dominated at temperature of within 250–290 ◦C. A Tmax-Tstop plot reveals not only horizontal regions but also smooth slopes, indicative of the presence of a continuum distribution of glow peaks and trap depth. A computerised glow curve deconvolution analysis of the respective ﬁbre glow-curves demon-strated that they were composed of ﬁve strongly overlapping peaks underlying a broad TL spectrum, obtaining ﬁgures of merit in the range of 0.56–1.64. The main physical kinetic parameters (activation energy and fre-quency factor) of the ﬁtted glow peaks were obtained using GlowFit software. The data suggest that the TL glow peaks of the Ge-doped silica optical ﬁbres obey second-order kinetics.